2015
DOI: 10.1134/s1063782615060056
|View full text |Cite
|
Sign up to set email alerts
|

Hopping transport in the space-charge region of p-n structures with InGaN/GaN QWs as a source of excess 1/f noise and efficiency droop in LEDs

Abstract: It is shown that the emission efficiency and the 1/f noise level in light emitting diodes with InGaN/GaN quantum wells correlate with how the differential resistance of a diode varies with increasing current. Analysis of the results shows that hopping transport via defect states across the n type part of the space charge region results in limitation of the current by the tunneling resistance at intermediate currents and shunting of the n type barrier at high currents. The increase in the average number of tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been pointed out in many literatures [11,[15][16][17][18][19][20][21][22] that the trap-assisted tunneling current is the main component of the GaN-based LED current when it is biased forward at low voltage (generally less than its turn-on voltage). Recently, it was shown that Hurkx's trap-assisted tunneling model [24] might have been applied to GaN PN junctions [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out in many literatures [11,[15][16][17][18][19][20][21][22] that the trap-assisted tunneling current is the main component of the GaN-based LED current when it is biased forward at low voltage (generally less than its turn-on voltage). Recently, it was shown that Hurkx's trap-assisted tunneling model [24] might have been applied to GaN PN junctions [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the degradation mechanism of 1/f noise in GaN multiquantum-well blue LEDs caused by c radiation is studied. Often, a typical I-V curve of GaN-based LEDs can be divided into three regions when they operate at the forward bias [11,[15][16][17][18][19][20][21][22],that is, the tunneling current region, the diffusion-recombination current region, and the series resistance region. e mechanism of current and 1/f noise in these three parts is different, so the degradation mechanism after c radiation may be different.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 1/f noise has been found suitable for the study of the physical mechanisms of degradation caused by radiation. There are many studies on low-frequency noise characterization of GaN-based LEDs [12][13][14][15][16]. Nevertheless, there are very few papers in which the degradations of 1/f noise caused by γ radiation in LEDs are investigated.…”
Section: Introductionmentioning
confidence: 99%